Engineered Glycocalyx Regulates Stem Cell Proliferation in Murine Crypt Organoids. Issue 4 (19th April 2018) - Rouhanifard, Sara H.; Lopez Aguilar, Aime; Meng, Lu; Moremen, Kelley W.; Wu, Peng
Summary: At the base of the intestinal crypt, long-lived Lgr5 + stem cells are intercalated by Paneth cells that provide essential niche signals for stem cell maintenance. This unique epithelial anatomy makes the intestinal crypt one of the most accessible models for the study of adult stem cell biology. The glycosylation patterns of this compartment are poorly characterized, and the impact of glycans on stem cell differentiation remains largely unexplored. We find that Paneth cells, but not Lgr5 + stem cells, express abundant terminal N -acetyllactosamine (LacNAc). Employing an enzymatic method to edit glycans in cultured crypt organoids, we assess the functional role of LacNAc in the intestinal crypt. We discover that blocking access to LacNAc on Paneth cells leads to hyperproliferation of the neighboring Lgr5 + stem cells, which is accompanied by the downregulation of genes that are known as negative regulators of proliferation. Graphical Abstract: Highlights: LacNAc is abundant on Paneth cells and can be edited in crypt organoids LacNAc blocking on Paneth cells leads to hyperproliferation of Lgr5 + stem cells Abstract : Rouhanifard et al. present a method for glycan engineering in a crypt organoid system and apply it to assess functions of N -acetyllactosamine (LacNAc) in stem cell biology. Results suggest that Paneth cells express high levels of LacNAc, and that blocking access to it leads to hyperproliferation of neighboring Lgr5 + stem cells.